2005
DOI: 10.1182/blood-2004-12-4973
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hydroxyurea therapy for infants with sickle cell anemia: the HUSOFT extension study

Abstract: The long-term efficacy and toxicity of hydroxyurea for infants are undefined, and its role in preventing organ dysfunction is unknown. Short-term feasibility of hydroxyurea administration, toxicities, hematologic effects, and effect on spleen function in infants with sickle cell anemia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
222
3
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(246 citation statements)
references
References 39 publications
9
222
3
12
Order By: Relevance
“…Shortly after the early phase hydroxyurea trials were completed in adults, several phase II trials established the tolerability and potential efficacy of hydroxyurea therapy in infants [52], toddlers [53], and older children [54]. The definitive benefits of hydroxyurea therapy in decreasing SCD related morbidity were replicated in children with hemoglobin SS (HbSS) or hemoglobin Sb(0)thalassaemia in a NHLBI sponsored study, the Hydroxyurea to Prevent Organ Damage in Children with Sickle Cell Anemia (BABY HUG) trial.…”
Section: Hydroxyurea Therapymentioning
confidence: 99%
“…Shortly after the early phase hydroxyurea trials were completed in adults, several phase II trials established the tolerability and potential efficacy of hydroxyurea therapy in infants [52], toddlers [53], and older children [54]. The definitive benefits of hydroxyurea therapy in decreasing SCD related morbidity were replicated in children with hemoglobin SS (HbSS) or hemoglobin Sb(0)thalassaemia in a NHLBI sponsored study, the Hydroxyurea to Prevent Organ Damage in Children with Sickle Cell Anemia (BABY HUG) trial.…”
Section: Hydroxyurea Therapymentioning
confidence: 99%
“…[1][2][3][4] Although hydroxyurea therapy and chronic red blood cell transfusion may decrease the complications of chronic organ damage, 5,6 both treatment modalities require long-term compliance to prevent irreversible end-organ damage. Currently, however, hematopoietic stem cell transplantation (HCT) provides the only cure for SCD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been carried out in children with sickle cell anemia, showing the clinical efficacy and short/middle-term safety of HU [169][170][171][172]. In this context, particularly important were the two Hydroxyurea Safety and Organ Toxicity (HUSOFT) studies.…”
Section: Butyratementioning
confidence: 99%
“…Hydroxyurea was shown also to be able to reduce the incidence of secondary stroke in children with sickle cell anemia and stroke [173]. The results of these two studies provided evidence that infants with sickle cell anemia tolerate HU therapy (up to 6 years of treatment) with sustained hematologic benefits, improved growth, and possibly preserved splenic function [169,170]. Importantly, the studies carried out in children showed that HU induces HbF levels to twice the average level achieved in adults [169][170][171][172].…”
Section: Butyratementioning
confidence: 99%
See 1 more Smart Citation